Pembatalan Akta SKMHT oleh Pengadilan yang Bersumber dari Pewarisan Dampak Legal Standing - Syafira, Raisa Putri; Sembiring, Rosnidar; Suprayitno, Suprayitno (Universitas Medan Area, 2024)
This article discusses the cancellation of the SKMHT deed (Power of Attorney to Encumber Mortgage Rights) by the court which originates from inheritance. SKMHT is a power of attorney given by the debtor to the creditor to place a mortgage on the land and/or building which is used as collateral for the credit. Cancellation of the SKMHT can occur if the SKMHT is not implemented within a certain period or if the SKMHT does not meet the applicable legal requirements. This article also discusses the impact of legal standing in the context of SKMHT cancellation that originates from inheritance. Legal standing is the authority or legal capacity of a person or legal entity to file a lawsuit or petition in court. Legal complexity in the context of inheritance can affect the legal position of the parties involved in SKMHT, whether as debtors, creditors, heirs, or third parties. This article digs deeper into conflicts, disputes, and lawsuits that may arise as a result of the cancellation of SKMHT by the court which originates from inheritance.